An empirical method to compensate the NMR calibrated porosity of the tight volcanic rocks based on comprehensive laboratory studies - Xiao, Yufeng; Ge, Xinmin; Xiao, Gaojie; Wang, Chengrong; Xu, Hongjun; Xiao, Juanjuan; Kang, Chujuan (Frontiers in Earth Science, 2023)
The nuclear magnetic resonance (NMR) response is known to deviate from the true value for the volcanic reservoirs, particularly when the pore throat size is ultralow. Consequently, the related petrophysical parameters such as porosity, permeability, as well as pore size distribution from NMR measurements are greatly influenced. An empirical method to correct the NMR calibrated porosity for the tight volcanic rocks is proposed after comprehensive investigations of influential factors combined with mineralogical and petrophysical analysis. The laboratory result indicates that the relative porosity deviation is negatively correlated with the geometric mean of the transversal relaxation time (T2), but positively correlated with the clay content. Moreover, both the paramagnetic materials such as manganese (Mn) content and the diamagnetic materials such as magnesium (Mg) content contribute to the NMR relaxation intensity reduction, but with different mechanisms. The NMR calibrated porosity can be compensated through multiple regressions with these controlling factors, which can be generalized to other tight volcanic reservoirs.